Diagnostic Value of Multiplex Polymerase Chain Reaction in Detection of Acinetobacter baumannii, Pseudomonas aeruginosa, and Stenotrophomonas maltophilia from Sepsis in Pediatrics - Galeb, Sara; Zaki, Maysaa E. S.; Shrief, Raghdaa; Hassan, Rasha; Rizk, Mohamed (Recent Patents on Biotechnology, 2021)
Background: Proper identification of the causative organism in pediatric sepsis is crucial for early diagnosis and prevention of septic shock and organ failure. Objectives: The aim of the present study was to evaluate the multiplex polymerase chain reaction (PCR) for detection of Acinetobacter baumannii, Pseudomonas aeruginosa, and Stenotrophomonas maltophilia from positive blood cultures for these pathogens isolated from children with hospital- acquired sepsis compared to the conventional biochemical reactions for identification of these organisms. Methods: This study was a cross-sectional study performed on 100 isolates from pediatric blood cultures, including Acinetobacter baumannii, Pseudomonas aeruginosa, and Stenotrophomonas maltophilia. The study also included 100 isolates of Escherichia coli as a negative control. All isolates were identified by API 20NE and the multiplex PCR with primers specific to the 3 tested bacteria. Results: Multiplex PCR was positive in 96% of isolates and 4 isolates had negative results. Falsepositive results were reported with three E. coli strains. Multiplex PCR identified all the isolates of Acinetobacter baumannii, 29 isolates of Pseudomonas aeruginosa and 27 isolates of Stenotrophomonas maltophilia. The diagnostic value of the multiplex PCR compared to the biochemical identification revealed sensitivity 96.04%, specificity 96.9%, positive predictive value 97.00%, negative predictive value 96.00% and accuracy 96.50%. Conclusion: The present study highlights the diagnostic value of multiplex PCR to identify Acinetobacter baumannii, Pseudomonas aeruginosa, and Stenotrophomonas maltophilia from positive blood cultures. Multiplex PCR was sensitive, specific and accurate. The accuracy differs according to the organisms with 100% accuracy for Acinetobacter baumannii.
Keywords: PCR